Resistance training and the elderly : an investigation into psychological wellbeing and life satisfaction : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Barker, Kevin Maxwell (Massey University, 2005)
This exploratory study examined the psychological benefits of high-intensity resistance training in an elderly age group. Participants in the sample (N=76) aged between 70-80, were randomly allocated to two groups (37 exercisers- 18 female and 19 male; 39 controls- 20 female and 19 male). Both groups completed five self-report questionnaires measuring psychological variables. The Purpose in Life Test (PIL), Profile of Mood States (POMS), State-Trait Anxiety Inventory (STAI), Affectometer 2, Rosenbergs Self-Esteem Scale (RSES) and a Dynamometer hand-grip strength test were administered pre-test, mid-test and post-test .The independent variable in this study was a 12 week high-intensity resistance training programme especially designed for this age group and supervised by qualified instructors at a commercial gymnasium. Repeated measures ANOVA produced results that indicated a high intensity resistance training programme provided strength gains, and improved some aspects of psychological wellbeing and life satisfaction components in older adults. There are positive indications from this study that this format of planned exercise can assist in the promotion of life quality enabling adaptation to changing situations often accompanying increasing age.
Keywords: Exercise for older people -- Psychological aspects; Isometric exercise